F cell numbers are associated with an X‐linked genetic polymorphism and correlate with haematological parameters in patients with sickle cell disease. (19th October 2020) - Urio, Florence; Nkya, Siana; Rooks, Helen; Mgaya, Josephine A.; Masamu, Upendo; Zozimus Sangeda, Raphael; Mmbando, Bruno P.; Brumat, Marco; Mselle, Ted; Menzel, Stephan; Luzzatto, Lucio; Makani, Julie
Summary: Patients with sickle cell disease (SCD) with high fetal haemoglobin (HbF) tend to have a lower incidence of complications and longer survival due to inhibition of deoxyhaemoglobin S (HbS) polymerisation by HbF. HbF‐containing cells, namely F cells, are strongly influenced by genetic factors. We measured the percentage of F cells (Fcells%) in 222 patients with SCD to evaluate the association of (i) Fcells% with genetic HbF‐modifier variants and (ii) Fcells% with haematological parameters. There was a different distribution of Fcells% in females compared to males. The association of the B‐cell lymphoma/leukaemia 11A ( BCL11A ) locus with Fcells% (β = 8·238; P  < 0·001) and with HbF% (β = 2·490; P  < 0·001) was significant. All red cell parameters except for Hb and mean corpuscular Hb concentration levels in males and females were significantly different. The Fcells% was positively associated with mean cell Hb, mean cell volume and reticulocytes. To explain the significant gender difference in Fcells%, we tested for associations with single nucleotide polymorphisms on the X chromosomal region Xp22.2, where a genetic determinant of HbF had been previously hypothesised. We found in males a significant association with a SNP in FERM and PDZ domain‐containing protein 4 ( FRMPD4 ) and adjacent to male‐specific lethal complex subunit 3 ( MSL3 ). Thus, we have identified an X‐linked locus that could account for a significant fraction of the Fcells% variation in patients with SCD.